Salivary and blood plasma oxytocin after oxytocin injection and during machine milking in dairy cows - Olga Wellnitz; Benjamin Jenni; Natascha Stoffel; Samantha Weber; Selma Aybek; Rupert M. Bruckmaier (JDS Communications)
Oxytocin (OT), the peptide hormone whose release from the pituitary is essential to induce milk ejection, has been measured in blood plasma of dairy cows for decades. In the present study we tested the possible use of saliva instead of blood sampling to record OT release by using a commercially available ELISA for salivary OT measurement both in saliva and blood plasma. Measurements were performed to detect the expected OT increase in response to intravenous OT injections and during machine milking. Three dairy cows were injected with increasing dosages (0.5, 1, 5, and 10 IU i.v.) of OT, and blood and saliva samples were repeatedly taken during 1 h after injection. Furthermore, 5 cows were milked and blood and saliva samples were taken during and until 20 min after milking. To verify the expected release of OT during milking, we used our established RIA for measurements in plasma in parallel to ELISA measurements. Our results showed that the commercial ELISA kit used was able to detect the OT concentrations in both saliva and plasma. The massive increase of OT concentration after OT injection and during milking could be detected in plasma with both RIA and ELISA. However, we did not observe any change of salivary OT within the duration of the experiments. Our results showed that short-term increases in blood plasma OT, such as in response to OT injection or milking, were not reflected by increasing salivary OT concentrations.